JURIDIC REVIEW ON CRIME OF MEDICAL MALPRACTICE - Akhiruddin Ahmad (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2022)
Research objectives are certain things to be achieved in a study. The research objectives will provide direction in the implementation of the research. The objectives of this research are 1). To find out the regulation regarding medical malpractice in the Indonesian legal system. 2). To obtain answers to problems regarding the juridical provisions on the occurrence of medical malpractice in accordance with the Indonesian legal system. The results of this study are the implementation of granting remissions for prisoners of criminal acts of corruption in Correctional Institutions has been carried out properly in accordance with applicable laws and regulations, but with the policy of the Minister of Law and Human Rights of the Republic of Indonesia concerning a moratorium on granting rights to prisoners of criminal acts of corruption, which was followed up by the issuance of a letter Circular of the Director General of Corrections, it can be concluded that remissions for convicts of criminal acts of corruption will be eliminated. However, the Penitentiary still proposes general remission (August 17) and special remission (Eid Al-Fitr) in 2012 on the grounds that the inmates have fulfilled the requirements. the requirements are in accordance with the provisions of Government Regulation Number 28 of 2006 concerning Terms and Procedures for the Implementation of the Rights of Correctional Inmates. The moratorium on granting remissions for convicts of criminal acts of corruption is contrary to the correctional system. Remission is a right for every convict and criminal child, remission is a form of government responsibility in fulfilling the rights of prisoners in prison.